1987
DOI: 10.3168/jds.s0022-0302(87)80080-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varying the Amounts of Dietary Calcium on Selenium Metabolism in Dairy Calves

Abstract: Influence of dietary Ca on Se metabolism was studied with 16 intact male Holstein calves averaging 86 kg. Calves were assigned randomly and fed one of four diets containing, .17, .67, 1.31, and 2.35% Ca at 3% of their body weight for 4 wk. The diets contained .062 ppm Se and .34% P. Four days prior to the end of the experiment, calves were dosed orally with radioactive 75Se. Dietary Ca had no significant effect on 75Se absorption. There was a slight curvilinear relationship between apparent 75Se absorption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Care (1994) also reported that higher dietary Ca levels decreased Mg absorption in cows. Lower bioavailability of Mg in response to higher dietary Ca levels was also reported by Alfaro et al (1987). Verdaris and Evans (1976) reported Mg absorption and retention (percent of intake) was higher in Holstein cows fed on diets low in Ca (0.2% vs 2.1%).…”
Section: Calcium and Phosphorus (Levels And Ratios)supporting
confidence: 56%
See 1 more Smart Citation
“…Care (1994) also reported that higher dietary Ca levels decreased Mg absorption in cows. Lower bioavailability of Mg in response to higher dietary Ca levels was also reported by Alfaro et al (1987). Verdaris and Evans (1976) reported Mg absorption and retention (percent of intake) was higher in Holstein cows fed on diets low in Ca (0.2% vs 2.1%).…”
Section: Calcium and Phosphorus (Levels And Ratios)supporting
confidence: 56%
“…While Ca may not have direct effect on Zn absorption, it can decrease Zn absorption in the presence of phytate (Oberleas et al, 1996). Other than Zn and Selenium, little information is available on effects of dietary Ca levels on other trace elements absorption in dairy cows (Harrison and Conrad;1984;Alfaro et al, 1987). At higher dietary Ca levels, a negative interaction with Zn absorption is possible.…”
Section: Introductionmentioning
confidence: 99%
“…However, neither Cu (Rahim et al 1986, Koenig et al 1989), Fe, Cd, Mo, Mn (Rahim et al 1986) nor Co (van Ryssen et al 1987) affected selenite absorption. Absorption of selenium may be decreased on low or high calcium intake (Alfaro et al 1987), with the optimal dietary calcium level being 8 g/kg DM for selenium absorption in the dairy cow (Harrison and…”
Section: Factors Affecting Se Absorptionmentioning
confidence: 99%
“…Se from the analysis of liver was lower than that determined from the analysis of serum ( On the other hand, Alfaro et al (1987) reported that dietary Ca (0. l7 -2.35 %) had no effect on /)Se absorption in dairy calves. White et al (1981) reported no significant effect of supple- …”
mentioning
confidence: 93%